The Effect of Control Locus, Professional Commitment, and Professional Ethics against Auditors Behavior in The Face of Audit Conflicts - N M Sri Yadnya Wati; I B Anom Yasa; N W Dewinta Ayuni (Journal of Applied Sciences in Accounting, Finance, and Tax, 2020)
Auditor behavior in the face of audit conflicts is an auditor’s action or behavior at the extent to which the auditor is willing to accept client pressure in conflict situations, that is a situation that occurs when auditors and clients disagree in an attestation function which is an indication of auditor behavior in decision making. Auditor behavior in the face of audit conflicts is influenced by various factors such as locus of control, professional commitment, and professional ethics. This study aims to examine the effect of locus of control, professional commitment, and professional ethics on auditor behavior in the face of audit conflicts. Population in this research is all public accounting firm exist in Bali which have been registered in directory of IAPI 2019. This research uses saturated sample or census sample method. The number of respondents used is 68 respondents. The hypothesis was tested with a significance level of 5% (percent). Using Partial Least Square though the Smart PLS 3.0 application. The result shows that the locus of control, professional commitment, and professional ethic has a significant effect on auditor behavior in the face of audit conflicts.